Effects of surface roughness on rotating cylinder and magnus wind turbine in low wind speed conditions - Marzuki, Omar Faruqi (2017)
In today’s world, every functional society depends on electricity. As electricity becomes essential in daily life, demand for sustainable energy increases. However, countries with low wind velocity like Malaysia are unable to use conventional wind turbine for energy extraction. This is due to the absence of high wind velocity required to generate high torque that will rotate the generator of the conventional wind turbine. To extract wind energy from low wind velocity countries, Magnus wind turbine (MWT) that utilizes rotating cylinder was experimentally studied. MWT utilized rotating cylinder blades to harvest wind energy by generating Magnus force perpendicular to the incoming air. Furthermore, a simple surface roughness enhancement will increase the force generated from the rotating cylinder. One of the problems with MWT is that the effect from using enhancement of surface roughness on the rotating cylinder blades on Magnus force and torque generated has not been fully characterized and documented. The studies also included force balance for scaling effect on rotating cylinder size and the smoke flow visualization for visual inspection of boundary layer. Therefore, this research will provide valuable information regarding sanded surface roughness application on MWT through experimental study. The MWT and single rotating cylinder are designed and fabricated based on past researches and patents. All experiments were carried out in a wind tunnel. The proof on concept experiment showed that rotating cylinder produced higher lift force compared to the airfoil under similar condition. Next, force balance experiment demonstrated that as rotating cylinder scale increased, the Magnus force generated also significantly increased. The most significant finding is that the surface roughness enhancement increased the small scale rotating cylinder performance making it to be on par with large scale rotating cylinder. The smoke flow visualization experiment illustrated that by using surface roughness enhancement, the boundary layer separation point is further shifted upstream and since it opposed the incoming wind flow, pressure region and the Magnus force are also increased. Moreover, MWT model was subjected to smooth surface and eight types of surface roughness enhancement on the rotating cylinder blades. The result shows that as frequency of rotation cylinder blades and wind speed increased, depending on surface roughness enhancement used, the torque generated will increase. Furthermore, the result shows that minimum cut-in wind speed is required to rotate the rotor as the velocity ratio and relative roughness increased. In summary, the outcome shows significant improvement of the effect of sanded surface roughness on the rotating cylinder blades. The sanded surface roughness produces five times higher torque coefficient and rate of change torque in comparison with smooth surface roughness. Hence, scientific community will gain the benefits of the effect on rotating cylinder with sanded surface roughness and will be able to use this data for future research.